2018
DOI: 10.3390/en11102568
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modeling of Dynamic Behavior and Steering Ability of a Bottom Hole Assembly with a Bent-Housing Positive Displacement Motor Under Rotary Drilling Conditions

Abstract: Fully rotary drilling is one of many useful technologies used for the exploitation of petroleum and geothermal resources, but fully rotating drill-strings are extremely complicated. Therefore, according to the Hamilton principle, a non-linear coupled bottom hole assembly (BHA)-bit-formation-wellbore model is proposed for BHAs with bent-housing positive displacement motor using the finite element method to investigate the dynamic behavior and steering ability under fully rotary drilling. The impact force, accel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 18 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…On the basis of the studies of drill string vibration and rockbreaking process, some researchers successfully combine the two to study the application of downhole tools and bottom hole assembly (BHA) (Dong and Chen, 2018a;Chen, et al, 2018). In these studies, the weight on bit (WOB) is applied to the upper end of drill string or the drill bit using an axial force, and the results are more interpretable.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the studies of drill string vibration and rockbreaking process, some researchers successfully combine the two to study the application of downhole tools and bottom hole assembly (BHA) (Dong and Chen, 2018a;Chen, et al, 2018). In these studies, the weight on bit (WOB) is applied to the upper end of drill string or the drill bit using an axial force, and the results are more interpretable.…”
Section: Introductionmentioning
confidence: 99%
“…Morin and Wilkens [23] reported that the bit tends to be perpendicular to the fracture strike in the drilling process and used the deviation logarithm to describe the trajectory of the borehole in three-dimensional space. Chen et al [24] proposed a bit formation wellbore model for a nonlinear coupled bottom borehole assembly under full screw drilling. Liu et al [25] established a linear elastic model of borehole collapse failure based on pore fluid seepage and obtained the attenuation law for the soft coal seam collapse pressure with gas seepage; the basic mechanical parameters of the coal seam and fluid seepage and the space of the borehole trajectory were also analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…e variable diameter stabilizer was developed and applied in the field [11,12]. In order to make the variable diameter stabilizer play a better role in the directional well, the variable diameter stabilizer was used in combination with the positive displacement motor, antiwear and antitorque tool [13][14][15]. However, the compound deflection of variable diameter stabilizer and BAH is seldom applied in the field, and the mechanism and model of the compound deflection are seldom studied in the application process.…”
Section: Introductionmentioning
confidence: 99%